Pola dan Strategi Dakwah dalam Moderasi Beragama - Abdul Mujib; Badrus Sholikhin (Institut Agama Islam Tribakti (IAIT) Kediri, 2022)
This paper is presented to provide readers with an understanding of how the pattern and strategy of da'wah. In the development of da'wah in Indonesia today has been faced with different things. Therefore, as a Muslim, it is necessary to make a pattern to facilitate the propagation of Islam. The strategy carried out is inseparable from the study of da'wah in the development of Islamic society. If we do not conceptualize this da'wah, the goals and desires in da'wah may not be achieved in accordance with what is expected. While in religious moderation, in every meeting they present romance and patterns in their respective religions. Although they have an interest in maintaining religious harmony. This also includes the potential for preaching to each religion. We know that even though every belief is and obligation for those who carry out a relationship with their God.